Venous thrombolysis prior to mechanical thrombectomy reduces glycocalyx damage in patients with acute ischemic stroke - Xu, Bin; Yin, Tengkun; Sun, Tanggui; Lv, Hang; Zhang, Wenyv; Zan, Xv; Hao, Jiheng; Wang, Jiyue; Zhang, Liyong (Frontiers in Neurology, 2024)
Introduction The administration of intravenous thrombolysis (IVT) before mechanical thrombectomy (MT) in the treatment of acute ischemic stroke (AIS) has been a subject of debate, and its potential benefits remain uncertain. This retrospective study aimed to investigate the effect of preoperative IVT on glycocalyx damage in patients with cerebral ischemia-reperfusion injury (IRI). Methods A cohort of 106 patients with acute large vessel occlusion in the anterior circulation treated with mechanical thrombectomy was enrolled. The levels of the glycocalyx damage marker, syndecan-1, were measured in the peripheral blood of these patients to assess glycocalyx damage during IRI, and clinical outcomes were compared between patients receiving MT alone vs. combined IVT and MT. Results The study results indicate that thrombolytic drugs have a significant impact on syndecan-1 levels in the blood. Compared to patients who underwent direct MT, those who received preoperative IVT had significantly lower levels of syndecan-1 in their blood. Although preoperative IVT did not alter the final clinical outcomes, the levels of syndecan-1 shedding reflect the extent of damage to the endothelial glycocalyx. Discussion This suggests that using thrombolytic drugs before mechanical thrombectomy may reduce endothelial glycocalyx damage in patients with ischemia-reperfusion injury. These findings provide indirect clinical evidence supporting the preoperative use of intravenous thrombolysis in such patients.